A tool for estimating antiretroviral medication coverage for HIV-infected women during pregnancy (PMTCT-ACT) - Bruce A. Larson; Nafisa Halim; Isaac Tsikhutsu; Margaret Bii; Peter Coakley; Peter C. Rockers (BMC, 2019)
Abstract Background In the typical prevention of mother to child transmission (PMTCT) of HIV cascade of care discussion or analysis, the period of analysis begins at the first visit for antenatal care (ANC) for that pregnancy. This starting point is problematic for two reasons: (1) a large number of HIV-infected women are already on life-long antiretroviral therapy (ART) when presenting for ANC; and (2) women present to ANC at different gestational ages. The PMTCT ART Coverage Tool (PMTCT-ACT), which estimates the proportion of days covered (PDC) with ART, was developed to address each of these problems. Methods PDC is a preferred method to measure adherence to chronic medications, such as ART. For evaluating the PMTCT cascade of care, as indicated by PDC with ART over various time periods, a "starting point" based on a specific day before delivery must be defined that applies to all women (treatment experienced or naïve at the first ANC visit at any gestational age). Using the example of 168 days prior to delivery (24 weeks), PMTCT-ACT measures PDC with ART during that period. PMTCT-ACT is provided as a STATA do-file. Using an example dataset for two women (ID1 is treatment experienced; ID2 is treatment naïve), the details of each major portion of the tool (Parts 1-5) are presented. PMTCT-ACT along with the intermediate datasets created during the analysis are provided as supplemental files. Conclusions Evaluating the PMTCT cascade of care requires a standard definition of the follow-up period during pregnancy that applies to all HIV-infected pregnant women and a standard measure of adherence. PMTCT-ACT is a new tool that fits this purpose. PMTCT-ACT can also be easily adjusted to evaluate other ante- and post-natal periods (e.g., final 4 weeks, final 8 weeks, complete pregnancy period, initial 24 weeks postpartum, time periods consistent with infant HIV testing guidelines).